Parola scenica: towards realism in Italian opera - Du Plessis, Hendrik Johannes Paulus (My University, 2008)
Abstract This thesis attempts to describe the emergence of a realistic writing style in nineteenth- century Italian opera of which Giuseppe Verdi was the primary architect. Frequently reinforced by a realistic musico-linguistic device that Verdi would call parola scenica, the object of this realism is a musical syntax in which neither the dramatic intent of the text nor the purely musical intent overwhelms the other. For Verdi the dramatically effective depiction of a ‘slice of a particular life’—a realist theatrical notion—is more important than the mere mimetic description of the words in musical terms—a romantic theatrical notion in line with opera seria. Besides studying the device of parola scenica in Verdi’s work, I also attempt to cast light on its impact on the output of his peers and successors. Likewise, this study investigates how the device, by definition texted, impacts on the orchestra as a means of realist narrative. My work is directed at explaining how these changes in mood of thought were instrumental in effecting the gradual replacement of the bel canto singing style typical of the opera seria of Rossini, Donizetti, and Bellini, by the school of thought of verismo, as exemplified by Verdi’s experiments. Besides the work of Verdi and the early nineteenth-century Italian operatic Romanticists, I touch also briefly on the oeuvres of Puccini, Giordano and the other veristi.
Keywords: parola scenica; realismin Italian opera